2015
DOI: 10.1115/1.4032093
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Harnessing the Metastable States of a Modular Metastructure for Programmable Mechanical Properties Adaptation

Abstract: Recent studies on periodic metamaterial systems have shown that remarkable properties adaptivity and versatility are often the products of exploiting internal, coexisting metastable states. Motivated by this concept, this research develops and explores a local-global design framework wherein macroscopic system-level properties are sought according to a strategic periodic constituent composition and assembly. To this end and taking inspiration from recent insights in studies of multiphase composite materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…3, we noticeably observed the correlation between dynamics of the first bistable element with respect to the transmission ratio (TR) under forward actuation. This is mainly for two reasons: first is the weak coupling between the individual units (to maintain adaptable and metastable characteristics, strong coupling is not desired [33] [34]) and second is because the driving frequency is inside the stopband, vibration is prone to be localized closer to the excitation initially. Therefore, we propose to predict the onset of supratransmission of the fully nonlinear metsatructure by analyzing an equivalent but simplified mathematical model that only retains the nonlinear element of the first unit while linearizing the rest of the chain.…”
Section: Predicting the Onset Of Supratransmission And Region Of Non-mentioning
confidence: 99%
See 1 more Smart Citation
“…3, we noticeably observed the correlation between dynamics of the first bistable element with respect to the transmission ratio (TR) under forward actuation. This is mainly for two reasons: first is the weak coupling between the individual units (to maintain adaptable and metastable characteristics, strong coupling is not desired [33] [34]) and second is because the driving frequency is inside the stopband, vibration is prone to be localized closer to the excitation initially. Therefore, we propose to predict the onset of supratransmission of the fully nonlinear metsatructure by analyzing an equivalent but simplified mathematical model that only retains the nonlinear element of the first unit while linearizing the rest of the chain.…”
Section: Predicting the Onset Of Supratransmission And Region Of Non-mentioning
confidence: 99%
“…V, influence of some key parameters on the threshold amplitude to trigger supratransmission is explored. In general, for a fixed global displacement , a chain of metastable modules can have up to 2 metastable states (internal configurations), Figure 1(c) [33] [34]. Starting from one of the metastable states, equations of motion for the ℎ metastable module can be expressed as:…”
mentioning
confidence: 99%
“…In addition, metamaterial or metastructure is a class of synthetic materials and its macroscopic properties can be artificially controlled to obtain a new type of material or structure with exotic properties, such as mechanical metamaterial, acoustic metamaterial, and thermal metamaterial (Harne et al, 2016). The special properties of metamaterial or metastructure are achieved by engineering its cellular architecture and chemical composition (Cui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies suggested that multistability can be exploited to achieve shape morphing (Daynes and Weaver, 2013;Haghpanah et al, 2016;Lachenal et al, 2013;Sun et al, 2016), broadband vibration control (Johnson et al, 2014(Johnson et al, , 2013Yang et al, 2014), robust sensing (Harne and Wang, 2014), energy harvesting (Daqaq et al, 2014;Harne and Wang, 2013), impact energy trapping (Frenzel et al, 2016;Puglisi and Truskinovsky, 2002;Shan et al, 2015), and even non-reciprocal wave propagations (Bilal et al, 2017;Nadkarni et al, 2016;Raney et al, 2016). In particular, stiffness adaptation has also been demonstrated on multistable structures such as the asymmetric fiber composite laminates (Arrieta et al, 2014;Kuder et al, 2015) and muscle inspired modular assemblies (Harne et al, 2015;Wu et al, 2016). If the effective stiffness or modulus is designed to be different among these stable states, one only needs to supply the energy to initiate a switch between stable states to achieve a sustained stiffness adaptation.…”
Section: Introductionmentioning
confidence: 99%